ESTIMATION OF IMMUNE-HEMATOLOGICAL PARAMETERS OF FUR-BEARING ANIMALS IN TOXOCARIASIS - L. A. Napisanova; O. B. Zhdanova; I. I. Okulova; S. P. Ashihmin; Ju. A. Berezina; O. V. Chasovskih (Российский паразитологический журнал)
Objective of research:   To study the prevalence of toxocariasis in the Kirov region, the coproovoscopic investigations of domestic carnivorous and caged fur-bearing animals have been conducted.Materials and methods: Before and after dehelmintization, the blood of carnivorous from fur farms of the Kirov region were tested. Blood tests of carnivorous were performed by standard hematological, crystalloscopic and immunological methods (ring-precipitation test with the BIEM antigen prepared from adult Toxocara parasites) using for the medical and biological analysis the software West Medica Produktionsund HandelsGmbH.The registration of the efficacy of dehelmintization was carried out by coproovoscopy of feces before and 10 days after giving the anthelmintic using the counting chamber VIGIS (Kotel'nikov G.A., Migacheva L.D., 1987)Results and discussion: Helminth eggs in feces of carnivorous (polar fox, silver-black and red fox, mink) were examined by the flotation method of Fuelleborni before and after dehelmintization with tetramisole using the group method. During the coproovoscopic examination, Toxocara eggs were found in 0,5% of  anonymous fecal samples, in 0,1%  of fecal samples from domestic carnivorous, but in samples from caged fur animals this value ran up to 95,5% before the scheduled dehelmintization, and several days later went down to 92,2% in dehelmintized animals.Toxocara eggs were found in feces from all animals in the fur farm (polar fox, silver-black and red fox, raccoon dogs), in mustelids (polecat and mink) no Toxocara eggs were found. The antheklmintic has a therapeutic effect but it is not high enough. However, the immune-hematological  parameters approximated to normal values.